HEALTH PROMOTION IN EFFORTS TO INCREASE MEDICATION COMPLIANCE IN HYPETENSIVE PATIENTE: A LITERATURE REVIEW - NONE, FRANSISCA LISA; Musharyanti, Lisa (Jurnal Keperawatan Respati Yogyakarta, 2021)
Compliance to taking medication is one of the problems in disease control efforts, especially non-communicable diseases such as hypertension. Taking medication regularly is one of the keys to control hypertension. One of the efforts to improve medication adherence is health promotion. The purpose of this study is to determine the methods used in health promotion to increase medication adherence in hypertensive patients. This research is a literature review. Sources of research articles were taken from the PubMed, Science Direct, and the Cochrane Library database, with the keywords "medication compliance on hypertensive patient" and "health promotion on hypertension patient". A total of 3,466 articles were obtained from the initial search and from all these articles 8 articles were found that met criteria to be analyzed. The results of the article review show several health promotion models that can affect medication compliance in hypertensive patients, namely family support, Pender’s health promotion model, and mHealth-based health promotion. The methods used in health promotion to increase medication compliance in hypertensive patients are family support, Pender’s health promotion model and mHealth-based health promotion. Keywords: Compliance taking medication; Hypertension; Health Promotion